1997
DOI: 10.1177/019251397018003005
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Shifts in Family Sociology? Evidence From Three Decades of Family Textbooks

Abstract: This article explores paradigm shifts in family sociology from the 1960s to the 1990s using a thematic content analysis of 7 multiple-edition texts. Two competing views on theoretical developments are examined. David Cheal claims that challenges posed to structural functionalist hegemony resulted in theoretical pluralism and an end to this hegemony. Dorothy Smith argues that Parson's theoretical assumptions are so deeply embedded in the discourse of family sociology that they continue to govern major issues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Structural theorists reason that "the current economic system is no longer congruent with traditional family values," thus making the labels of "good" and "bad" parents even more unfair and restrictive (Dill et al, 1998, p. 9;Mann et al, 1997;Smith, 1993). This section comprises a brief review of some of the recent economic transformations in the U.S. We concentrate mostly on how the market economy is now global and few U.S. jobs are secure.…”
Section: Structural Transformations In the Economymentioning
confidence: 99%
“…Structural theorists reason that "the current economic system is no longer congruent with traditional family values," thus making the labels of "good" and "bad" parents even more unfair and restrictive (Dill et al, 1998, p. 9;Mann et al, 1997;Smith, 1993). This section comprises a brief review of some of the recent economic transformations in the U.S. We concentrate mostly on how the market economy is now global and few U.S. jobs are secure.…”
Section: Structural Transformations In the Economymentioning
confidence: 99%
“…41n a content analysis of three decades of family sociology textbooks' coverage of race, class, and gender, we found that those social movements that were most successful in institutionalizing some of their goals-namely the civil rights movement and the women's movement-saw their central issues of race and gender receive the most significant paradigmatic shifts in coverage (Mann, Grimes, Kemp, and Jenkins, 1997).…”
Section: Endnotesmentioning
confidence: 94%
“…In the original essay (Paré & Dillaway, 2005), we held that structural transformations of the economy were an essential force to understand, if we are to comprehend the social shifts within family and paid work activities (see also Baca Zinn & Eitzen, 2005;Dill et al, 1998;Mann et al, 1997;Newman, 1994;Rubin, 1994;Smith, 1993). In the years since we discussed the interconnection of these topics, individuals living in the U.S. have experienced a collapse of the housing market (in 2006) and a subsequent Great Recession (2007Recession ( -2009, with the latter described as the most impactful economic event that families have experienced since the Great Depression (Rose & Winship, 2009;Ellen, & Dastrup, 2012).…”
Section: Changes In the Economymentioning
confidence: 99%